1993
DOI: 10.1002/j.1537-2197.1993.tb13796.x
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Leaf Spectral Reflectance to Plant Stress

Abstract: Leafspectral reflectances were measured to determine whether leafreflectance responses to plant stress may differ according to the agent ofstress and species. As a result ofdecreased absorption by pigments, reflectance at visible wavelengths increased consistently in stressed leaves for eight stress agents and among six vascular plant species. Visible reflectance was most sensitive to stress in the 535-640-nm and 685-700-nm wavelength ranges. A sensitivity minimum occurred consistently near 670 nm. Infrared re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
324
1
6

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 388 publications
(365 citation statements)
references
References 13 publications
34
324
1
6
Order By: Relevance
“…3. The real values are presented in Table 2. foliar or canopy red reflectance could respond to stress with a consistent increase (Carter, 1993;Smith et al, 2004). However, the canopy reflectance of seepweed community at 680 nm in treatment M was only slightly higher compared with that in treatment L (Fig.…”
Section: Mechanisms and Potential For Monitoring Plant Stress Using Tmentioning
confidence: 91%
“…3. The real values are presented in Table 2. foliar or canopy red reflectance could respond to stress with a consistent increase (Carter, 1993;Smith et al, 2004). However, the canopy reflectance of seepweed community at 680 nm in treatment M was only slightly higher compared with that in treatment L (Fig.…”
Section: Mechanisms and Potential For Monitoring Plant Stress Using Tmentioning
confidence: 91%
“…Since the 1990s spectral reflectance measurement has been increasingly used as screening approach for the tolerance of various stresses (Carter 1993;Peñuelas and Filella 1998). For example, Winterhalter et al (2011) estimated canopy water mass of tropical maize hybrids based on spectral reflectance and showed that it can be used as a high throughput tool to discriminate between groups with different drought resistance.…”
Section: Breeding For Dehydration Avoidancementioning
confidence: 99%
“…In the digested material, total nitrogen and phosphorus were determined calorimetrically according to Murphy and Riley (1962), respectively and potassium was determined by Flame photometer as described by Cheng and Bray (1951). Micronutrients (Fe, Zn and Mn) leaf contents were determined by Perkin EL mer atomic absorption spectrophotometer according to Carter (1993). The concentration of N, P and K, were expressed as percent, while those of Fe, Zn and Mn were expressed as parts per million, on dry weight basis.…”
Section: Determination Of Leaf Minerals Compositionmentioning
confidence: 99%